2009
DOI: 10.4102/sajim.v11i4.413
|View full text |Cite
|
Sign up to set email alerts
|

Researchers' perspectives on open access scholarly communication in Tanzanian public universities

Abstract: This research explored the awareness, usage and perspectives of Tanzanian researchers on open access as a mode of scholarly communication. A survey questionnaire targeted 544 respondents selected through stratified random sampling from a population of 1088 university researchers of the six public universities in Tanzania. With a response rate of 73%, the data were analysed using the Statistical Package for Social Sciences. The study reveals that the majority of the researchers were aware of and were positive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 23 publications
(17 reference statements)
12
67
0
Order By: Relevance
“…The content created is African content and it is important for us to share this content locally and internationally. Dulle and Minishi-Majanja (2009) note that Africa only generates 0.4% of global content and adding resources to UCT OpenContent will be a first step in redressing this imbalance.…”
Section: Contextmentioning
confidence: 99%
“…The content created is African content and it is important for us to share this content locally and internationally. Dulle and Minishi-Majanja (2009) note that Africa only generates 0.4% of global content and adding resources to UCT OpenContent will be a first step in redressing this imbalance.…”
Section: Contextmentioning
confidence: 99%
“…In terms of content, 50% are interested in website updates, 25% accessing the e-library resources and about 23% read emails with very few (2%) visiting the website for monitoring students' progress reports. While poor research conditions have been reported to slow down open access usage [13], the results reveals high usage among scholars. Low content recruitment demotivates users because many institutional web pages are frequently out of date or incomplete [16].…”
Section: Web Usage Behaviormentioning
confidence: 89%
“…Adoption and awareness have been identified by various scholars around the world as the main factors that affect open access adoption and usage among institutions and scholars [13,15]. The other factor that has not received considerable attention is web usage behavior among scholars.…”
Section: Web Usage Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Dulle (2010) and Msonge (2013) observed that, library users in academic libraries in Tanzania complained of poor access to current library resources and difficulties for subscription to online scholarly content. This affected negatively teaching and learning process, research and consultation services.…”
Section: Relationship Of Academic Libraries and Its Users In Collectimentioning
confidence: 99%